IKAN GABUS DALAM KARYA SENI GRAFIS - YUDHA RAEYFALDO, Yofita Sandra, S.Pd., M.Pd., Drs. Irwan, M.Sn. (Universitas Negeri Padang, 2017)
The purpose of the creation of this final work is to visualize the greedy nature through the metaphor of cork in graphic artwork. The greediness becomes the main problem that many people now have so that someone can do anything to get what he wants. The method of creating artwork, using five stages of preparation stage, elaboration stage, synthesis stage, stage of concept realization and completion stage. Furthermore, there is an exhibition of graphic art work, a technique of serigraphy (stencil print) that exposes the colors in accordance withthe object. Through this graphic work, the author displays all the anxiety that is felt. The theme of greed problems with metaphor of cork in graphic artwork with the title: (1) Keluar Batas , (2)Rebutan, (3) Diam-Diam, (4) Terperangkap, (5) Sulit, (6) Kurang, (7) Makan Anak, (8) Dapat, (9) Nafsu, (10) Persaingan.Key words : Fish Cork, Graphic Art, Serigraphy (stencil print)